MORPHOLOGICAL AND HISTOLOGICAL IDENTIFICATION OF “FASCIOLA GIGANTICA” RECOVERED FROM LIVER OF INFECTED BUFFALOES - Pandya; Hasnani; P. V., Patel (International Journal of Research -GRANTHAALAYAH, 2015)
This study was undertaken to identify Fasciolagiganticai on the basis of its morphology and histology to be the common cause of fasciolosis in infected buffaloes. Material & Method: Adult liver flukes were recovered from the liver of naturally infected buffaloes slaughtered in various abattoirs in Gujarat. Some adult flukes were flattened, put between two slides , pressed and stained in Borax carmine, and some flukes were sectioned in the median sagittal plane and histological slides of the flukes were prepared for detailed morphological and histological studies. Result: Microscopic pictures of the parasite used in identification defines the similarity in the morphology and histology of the F. gigantica on the basis of morphology of flukes; anterior sucker, posterior sucker (acetabulum), pharynx, uterus, ovary and type of epithelium. Conclusion: It can be concluded that the most common species found in buffaloes infected with Fasciolagigantica on the basis of its histo-morphological appearance in Gujarat.